A splenic hamartoma: Adding a new case to the literature: A case report. (January 2022) - Sabra, Tarek Abdelazeem; Maher, Ahmed; AlRashidi, Rahf; Ibrahim, Hussein
Abstract: Introduction: Splenic tumours are relatively rare and include malignancies such as lymphomas, angiosarcomas, plasmacytomas, primary malignant fibrous histiocytomas, and splenic metastases. Benign tumours of the spleen such as hemangiomas, cysts, and inflammatory pseudotumours are very rare (Kaza et al., 2010, PisaniCeretti et al., 2012) [1, 2] . There are fewer than 160 cases of splenic hamartoma or splenomas having been reported in the literature (Basso et al., 2012) [3]. Only 20% of the cases were detected in children (Abramowsky et al., 2004) [4]. Although multi-modality imaging findings were described preoperatively, the final diagnosis was splenic hamartoma based on histology and immunohistochemistry. Case report: Here, we report a case of a14 year old child left upper quadrant abdominal pain and worsening sickness. Multi-modality imaging detected a solid lesion of the spleen, who required splenectomy and was pathologically diagnosed as a splenic hamartoma. The postoperative course was uneventful. Discussion: Splenic hamartoma is very rare. Only 20% of hamartomas occur in children. They are commonly found incidentally on imaging with no symptoms. Conclusion: Splenic hamartoma is a benign vascular proliferative lesion that requires a multi-modality imaging studies for diagnosis and confirmed by histopathology. It must be included in the differential diagnosis of splenic mass forming lesions. Highlights: There are fewer than 160 cases of splenic hamartoma having been reported in the literature. Only 20% of the cases were detected in children. Although imaging findings were described preoperatively, the final diagnosis was splenic hamartoma based on histology. We report a case of solid lesion of the spleen, who required splenectomy and was pathologically diagnosed as splenic hamartomas.